The Personal Debt Management Literacy for the Participants affiliated with Penabur Christian Education Agency Foundation in Cirebon - Peter, Peter; Iskandar, Dini; Herlina, Herlina; Martalena, Martalena; Wahyusaputra, Tedy; Hadianto, Bram (Abdimas Galuh, 2025)
This community service aims to make the participants associated with Penabur Christian Education Agency Foundation in Cirebon comprehend debt management by delivering knowledge of credit cards, pawnshops, pay-later, and online peer-to-peer lending platforms. Because of the numerous people, the keynote speaker utilizes the lecture technique to deliver them, followed by a question-and-answer section. Furthermore, this committee designed the related multiple choice questions through the questionnaire and asked the participants to complete them before and after the material delivery (MD) to know this effectiveness. As a result, 70.95% of precise answers exist after MD, elevated from 65.77% of precise ones before MD. This situation indicates that the participants understand this debt literacy well. Indeed, by having it, they can correctly decide the debt sources used to avoid financial problems.